2005
DOI: 10.1111/j.1460-2695.2005.00871.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of shot‐peening intensity on fretting fatigue crack‐initiation behaviour of Ti–6Al–4V

Abstract: A B S T R A C TThe effects of shot-peening intensity on fretting fatigue crack-initiation behaviour of titanium alloy, Ti-6Al-4V, were investigated. Three intensities, 4A, 7A and 10A with 100% surface coverage, were employed. The contact geometry involved a cylinder-on-flat configuration. Residual stress and improvement in fretting fatigue life were directly related to shot-peening intensity. The magnitude of compensatory tensile stress and its location away from the contact surface increased with increasing i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
35
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 28 publications
(73 reference statements)
1
35
0
Order By: Relevance
“…This can be due to plasticity in surface layers [85,98,99,109,111,118,119] or due to elevated service temperature [85,106,120]. For example, about 30% of the residual stresses generated by shot peening relaxed during a test at 260°C, resulting in a reduction in fretting fatigue life [85].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This can be due to plasticity in surface layers [85,98,99,109,111,118,119] or due to elevated service temperature [85,106,120]. For example, about 30% of the residual stresses generated by shot peening relaxed during a test at 260°C, resulting in a reduction in fretting fatigue life [85].…”
mentioning
confidence: 99%
“…The most common processes include shot peening [105][106][107][108][109][110][111][112], laser shock peening (LSP) [110,111,113], and low plasticity burnishing (LPB), also known as deep rolling [34,108,111,113,114]. Both LSP and LPB generate considerably deeper compressive residual stresses while inducing less cold work compared to shot peening.…”
mentioning
confidence: 99%
“…In the case of SP, the induced residual stress extended deeper into the specimen (Fig. 11) such that the effects of residual stress was retained up to a depth of about 180 lm from the contact surface which would prevent subsurface crack initiation, and it was the case in the actual tests [23]. Further, the maximum values of MSSR parameter are almost equal in both CSP and SP specimens.…”
Section: Resultsmentioning
confidence: 74%
“…For all three conditions of residual stresses (100% RS, 50% RS, and 0% RS), the maximum values of MSSR parameter were located at the contact surface. This suggests that crack would initiate at the contact surface in the shot peened specimen, which was the case in the actual tests [23]. It should be noted here that the complete residual stress relaxation state (0% RS) represents the untreated virgin specimen and it is same for CSP and SP specimens.…”
Section: Resultsmentioning
confidence: 94%
“…10. Many research studies [18,19] have reported that the surface damage will be more significant with increasing relative slip amplitude. It is also known that the combination of low tangential stress and high compressive stress at the contact edge will enhance FF strength and vice versa will reduce FF strength.…”
Section: Effect Of Rigidity Of Contact Pad On Ff Strengthmentioning
confidence: 98%